Program for the development of service-learning projects in secondary education - González, Esther Luna (2012)
Learning and Solidarity Service (LSS) are considered as a pedagogical strategy favorable to promote education for citizenship. On this assumption, the article starts with the elements that are the basis of the education for an active citizenship, critical and responsible, focusing mainly on its construction as from the participation. In the second part of the article that presents the preparation, the application and the evaluation of a program of Learning and Solidarity Service (LSS) put into practice in an institute of middle school teaching of the province of Barcelona (Spain). The program designed, applied and evaluated covers a range of activities that put at stake: a) the development of a living awareness of belonging to a community, learning a set of skills and attitudes to participate in it, and b) to facilitate a commitment to improve, promoting a sense of social responsibility; finally, the program fosters the citizen learning bound with the feeling of belonging, the citizen competences and active participation exposed in the first part of the article.